Amazonian deforestation and its influence on soil biotic factors and abiotic properties - Souza, Tancredo Augusto Feitosa de; Silva, Lucas Jónatan Rodrigues da [UNESP]; Nascimento, Gislaine dos Santos (Elsevier, 2023)
Deforestation in the Amazonian rainforest is the main cause of biodiversity loss, soil erosion, and climate change. Land covers influence the soil properties, soil biota community composition, and litter properties by providing habitat and nutrients. Our aim here was to present a quantitative analysis of the soil biochemical properties, soil biota assemblage, and litter properties associated with four land covers (primary Amazon rainforest, pasture, Hevea brasiliensis, and deforested sites) from the Brazil's Legal Amazon, Rio Branco, Acre. The non-metric multidimensional scaling (NMDS) grouped the land covers in four groups considering the dissimilarities on soil biota abundance between each other. The SEM models showed that deforestation increased the soil pH, and decreased SOC, TN, P, microbial N biomass, microbial C biomass, litter lignin content, litter N, C and P contents, and biodiversity indices (Margalef index, and α diversity). The results of our study highlighted the importance of considering land covers in Brazil's Legal Amazon, based on a sustainable way to improve soil quality and soil biodiversity, since even the studied monocropping system (pasture) showed decreases in habitat provision (litter deposition) and nutrient availability. Thus, the use of forest systems (H. brasiliensis) or the preservation of primary Amazon rainforest may positively influence the soil chemical properties, soil biota, and litter properties.
Keywords: Brazil's Legal Amazon; Litter properties; Plant-soil feedback; Soil biota diversity; Structural equation modelling